PARADIGMA BIMBINGAN DAN KONSELING: PERGESERAN ORIENTASI DARI TERAPEUTIK-KLINIS KE PREVENTIFPERKEMBANGAN - Sigit Sanyata (Paradigma, 2012)
Early development of counseling and psychotherapyis influenced by psychodynamic, respectively influencescognitive / behavioristik, and humanistic perspectives into theparadigm system of guidance and counseling. Paradigm shiftaimed at the effectiveness of guidance and counseling notprovide justification that the earlier theories are not well.Another important thing that must be understood by thecounselor are all theories of counseling and psychotherapy havecontributed in accordance with the concept and view of manwith the attributes of the Problem. Shift towards preventiveseensignificant growth for the period in which the learnersshould be given an equal opportunity to thrive.Key words : counseling and psychotherapy, paradigm system ofguidance and counseling